A Dilemma in Staging of Esophageal Cancer: How Should We Stage ypT0 N2 M0 Esophageal Cancer after Neoadjuvant Therapy?. (6th August 2015) - Celik, Sebahattin; Erten, Remzi; Batur, Abdulsamed; Suvak, Burak
Abstract : Background . Since neoadjuvant treatment in esophageal cancer began to become popular, a complete pathological response at the primary tumour site has been commonly reported. An issue of conflict is whether complete response in the esophageal lumen means that the esophagus is completely tumour-free. Another important issue is whether lymph nodes that are retrieved from pathologically complete response cases are also tumour-free or not. There is a gap in the esophageal cancer staging system for ypT0 N2 M0 tumours that have received neoadjuvant therapy. Here, we will discuss the problem about staging of esophageal cancer associated with neoadjuvant therapy. Case . A female aged 40 years complaining of dysphagia was diagnosed as having locally advanced thoracic esophageal cancer. Neoadjuvant therapy decision was taken by oncology committee. Six weeks after neoadjuvant therapy, with a curative intention, minimal invasive surgery was performed. The pathology report was as follows. "There were no neoplastic cells in the suspected area of the esophageal mucosa upon examination with all staining. There was no cancer at resection margins. Four metastatic lymph nodes were infiltrated with squamous cell cancer." Conclusion . Despite the growing use of neoadjuvant treatment in locally advanced esophageal cancer in world, we do not have a protocol for the evaluation of these patients' pathology reports. We believe that new studies and new ideas are needed to resolve this dilemma associated with neoadjuvant therapy.